Optimization of conditions for treatment of ZnSe crystal surfaces by chemical etching - Tomashyk, V.M.; Kravtsova, A.S.; Tomashyk, Z.F.; Stratiychuk, I.B.; Galkin, S.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
The process of chemical polishing the undoped and doped ZnSe crystals
surface with H₂O₂ – HBr etchants has been studied. The dependence of the samples
polishing rate on the concentration of H₂O₂ in HBr solution has been investigated.
Surface states after chemical etching have been established using electron and atomic
force microscopies, and it was shown that the surface state is improved after chemical
etching. Etchant selection to develop slow polishing compositions for chemicalmechanical
polishing the investigated materials has been made. Concentration regions of
polishing solutions have been found for various types of ZnSe surface treatment: to
remove the damaged layer, to control the etching rate, to obtain samples of a given
thickness.